A study on relationship between body-image and self-esteem among medical undergraduate students - Virk, Amrit; Singh, Parmal (International Journal Of Community Medicine And Public Health, 2020)
Background: Body image refers to how individuals think, feel and behave in relation to their body and appearance. During adolescence self-perception about their appearance is important to the development of self-esteem and is also understood to be an important predictor of self-worth. Research has shown that inappropriate perception of the body image and dissatisfaction can lead to physical and psychic problems in the youth. In today's society, with the growing sense of ideal body image, adolescents and young adults try to lose or gain body weight to attain perfect body. The objective of the study is to find out the proportion of students dissatisfied with their body image, and the association of various determinants with body image dissatisfaction and self-esteem. Methods: A cross-sectional study was done among 125 first year medical students located in rural Haryana. A semi-structured questionnaire was used to collect data on various determinants associated with body image dissatisfaction and self-esteem. Results: Body image dissatisfaction was present among 16.8% of the students. Low self-esteem was observed among 21.6% of the students. Low body mass index (<18.5) was found to be significantly associated with body image dissatisfaction. A moderately positive correlation (r=0.384, p<0.001) was observed between self-esteem and body image satisfaction. Conclusions: Study findings support the fact that body image dissatisfaction has its impact on self-esteem among college-going youth. It is imperative that effective interventions be planned to educate the youth on ideal body weight and protect this young generation from pressures and consequences of negative body image.